Scorpion Venom Antimicrobial Peptides Induce Caspase-1 Dependant Pyroptotic Cell Death - Elrayess, Ranwa A.; Mohallal, Mahmoud E.; Mobarak, Yomn M.; Ebaid, Hala M.; Haywood-Small, Sarah; Miller, Keith; Strong, Peter N.; Abdel-Rahman, Mohamed A. (Frontiers in Pharmacology, 2022)
Within the last decade, several peptides have been identified according to their ability to inhibit the growth of microbial pathogens. These antimicrobial peptides (AMPs) are a part of the innate immune system of all living organisms. Many studies on their effects on prokaryotic microorganisms have been reported; some of these peptides have cytotoxic properties although the molecular mechanisms underlying their activity on eukaryotic cells remain poorly understood. Smp24 and Smp43 are novel cationic AMPs which were identified from the venom of the Egyptian scorpion Scorpio maurus palmatus. Smp24 and Smp43 showed potent activity against both Gram-positive and Gram-negative bacteria as well as fungi. Here we describe cytotoxicity of these peptides towards two acute leukaemia cell lines (myeloid (KG1-a) and lymphoid (CCRF-CEM) leukaemia cell lines) and three non-tumour cell lines (CD34+ (hematopoietic stem progenitor from cord blood), HRECs (human renal epithelial cells) and HaCaT (human skin keratinocytes). Smp24 and Smp43 (4-256 µg/ mL) decreased the viability of all cell lines, although HaCaT cells were markedly less sensitive. With the exception HaCaT cells, the caspase-1 gene was uniquely up-regulated in all cell lines studied. However, all cell lines showed an increase in downstream interleukin-1IL-1 expression. Transmission electron microscope studies revealed the formation of cell membrane blebs and the appearance of autolysosomes and lipid droplets in all cell lines; KG1-a leukemia cells also showed the unique appearance of glycogen deposits. Our results reveal a novel mechanism of action for scorpion venom AMPs, activating a cascade of events leading to cell death through a programmed pyroptotic mechanism.